The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1177/0733464804267581
|View full text |Cite
|
Sign up to set email alerts
|

Factors Effecting Volunteer Ombudsman Effort and Service Duration: Comparing Active and Resigned Volunteers

Abstract: Volunteers are key to successful ombudsmen programs. Motivating them and keeping them is difficult. The principal goal of this article is to compare active and resigned volunteer ombudsman perceptions (along with select demographic influences) of factors that either encouraged or discouraged their work. The authors find that former ombudsmen felt more role ambiguity, greater nursing facility resistance, higher boredom, and desired better supervision than active volunteer ombudsmen. They also served less time i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The association between role conflict and role ambiguity with job satisfaction/dissatisfaction and withdrawal decisions has been widely reported across work settings (Kahn et al, 1964; Örtqvist & Wincent, 2006). Regarding nursing homes (NHs), one study found that role conflict was the most enervating stressor for active long-term care (LTC) Ombudsmen (Nelson, Netting et al, 2004). Ombudsmen, like NHAs, must balance resident autonomy with beneficence and face similar competing demands/expectations from families, staff, regulators, and others that are not always consistent with their resident rights–based focus.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The association between role conflict and role ambiguity with job satisfaction/dissatisfaction and withdrawal decisions has been widely reported across work settings (Kahn et al, 1964; Örtqvist & Wincent, 2006). Regarding nursing homes (NHs), one study found that role conflict was the most enervating stressor for active long-term care (LTC) Ombudsmen (Nelson, Netting et al, 2004). Ombudsmen, like NHAs, must balance resident autonomy with beneficence and face similar competing demands/expectations from families, staff, regulators, and others that are not always consistent with their resident rights–based focus.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Volunteer movement is inconceivable without a close connection with patriotic upbringing, as one of its basic directions (Nelson, Netting, Huber & Borders, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with pre-COVID-19 research, RC among NHAs is predictive of higher TI (Nelson et al, 2021). Research on other long-term care roles suggests that RC emerges as a “most discouraging factor” (Nelson et al, 2004, p. 318). This is arguably due to an inescapable plethora of fundamental NH “goal incompatibilities” (Nelson & Cox, 2004, p. 86).…”
Section: Discussionmentioning
confidence: 99%